The Importance of Expressing Politeness: English Education Student's Perspectives - Sholihatul Hamidah Daulay; Nabilah Azmi; Tara Pratiwi (Tarling : Journal of Language Education, 2022)
This study focuses on how important it is to apply politeness in speaking with someone from the perspective of English Education students. To do this research, researchers used qualitative methods. One of the techniques that researchers use in this study is the non-interactive technique that is the questionnaire. This questionnaire was chosen to explore deeper information about the opinions of English Education Students at State Islamic University of North Sumatera Medan starting from the 2nd – 8th Semester (participants or respondents) on the importance of expressing politeness. Researchers chose the questionnaire technique in order to shorten the time and got more participants rather than had to conduct interviews. This study reports the choice of being polite for people is influenced by differences in power relations, such as notion of status, age, gender, and social distance. This study emphasizes that politeness is needed to be implemented since rudeness creates conflict between one to another person.